Impelementasi Etika Profesi Guru di SMA Kristen Palangkaraya: Tantangan di Era Pembelajaran di Abad 21 - Dewi Rekha Natalia Situmorang; Triyani Triyani (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This Study aims to describe the implementation of teacher professional ethics at Palangkaraya Christian High School and identify the challenges faced the context of 21st century learning. Teacher professional ethics are a very important moral foundation in carrying out educational tasks, especially in an era marked by technological developments, globalization, and changes in students character. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that most teachers at palangkaraya Christian high school have implemented etchial values such as responsibility, integrity, fairness, and respect for students, However, there are significant challenges such as the digital literacy gap, ethical boundaries in the use of social media, and pressure to adapt learning methods to the characteristics of today’s students. Therefore, a sustainable strategy is needed to strengthen teacher professional ethics through training, character building, and collaboration between schools, parents, and the community.